STRUKTUR TULANG DAN OTOT SIRIP KAUDAL KOMPLEKS Andamia heteroptera Bleeker (IKAN AMFIBI) - Gatot Nugroho Susanto (BERITA BIOLOGI, 2019)
Andamia heteroptera, known as rockskipper fish, is one of amphibious fish. Most of amphibious fish use caudal fin to facilitate locomotion in land and water. The modification is fusion of os hypural and reduction-fusion os epural and uroneurals. The aim of this study was to  acces skeleton and musculature structure of A. heteroptera caudal fin. Alizarin red-Alcian blue staining revealed that caudal fin of A. heteroptera has wider spina hemalis and spina neuralis support the locomotion. There is modification of caudal fin structure for support the locomotion. Caudal fin musculature of A. heteroptera is identified as primitive type, since its lack of musculus hypochordal longitudinalis.